Trends in Fruit Quality Improvement From 15 Years of Selection in the Apple Breeding Program of Washington State University - Teh, Soon Li; Kostick, Sarah; Brutcher, Lisa; Schonberg, Bonnie; Barritt, Bruce; Evans, Kate (Frontiers in Plant Science, 2021)
Washington State University’s apple breeding program (WABP) was initiated in 1994 to select new apple cultivars with improved eating quality, appearance, and storability that are suitable for production in the main growing regions of the state. Fruit quality is phenotyped using various instrumental measures, such as penetrometers (texture), titrator (acidity), and refractometer (soluble solids concentration; SSC), as well as sensory assessment. WABP’s selection regime occurs in three sequential phases: phase one (P1) – single, unreplicated seedlings at one site, phase two (P2) – replicated selections at three geographically diverse sites, and phase three (P3) – highly replicated elite selections at one to two grower sites. Most of WABP’s data collection occurs in P2. Knowledge of trends/changes associated with advancing selections is essential for understanding selection criteria and progress of WABP throughout the changing compositions of advancing and culling selections. For each postharvest trait, P2 data from harvest years 2005 to 2019 were split across sites, and between selections and reference cultivars (e.g., Cripps Pink, Gala, Honeycrisp). Means of instrumental crispness and inner cortex firmness for the advancing selections increased gradually over this period and were significantly higher than those for cultivars. Means of outer cortex firmness measurements were stable for selections, but significantly higher than those for cultivars. Average fruit acidity of selections increased marginally over this period and was higher than that of cultivars. Meanwhile, average fruit SSCs of selections and cultivars were statistically indistinguishable. These 15-year trends indicate that WABP has been selecting for apples with improved eating quality and storability through increased crispness and inner cortex firmness, respectively.